Analisis Pengaruh Citra Merek dan Kualitas Produk Terhadap Loyalitas Pengguna Smartphone Android dengan Kepuasan Sebagai Variabel Intervening Di Lingkungan Mahasiswa Universitas Bandung Raya - Ruli Mochammad Chaerudin; Tatiek Ekawati Permana (Universitas Insan Cendekia Mandiri, 2019)
Abstract : Along with the development of the telecommunications industry in Indonesia, making communication both close and long distance communication becomes easier and smoother. Cellular phone (cellphone) is one of the communication technologies that has developed from year to year. The Android operating system is a Linux-based operating system designed for touch screen mobile devices such as smartphones and tablet computers. By providing a development platform that is open (open source), Android developers offer the ability to build applications that are very rich and innovative and of course very profitable for consumers because it is relatively freeware (most applications are free). This study tries to examine the effect of brand image and product quality on the loyalty of Android-based smartphone users in the University of Bandung Raya environment, both directly and indirectly through satisfaction as an intervening variable. This study uses a survey approach and the nature of this research is explanatory research. The population in this study were Bandung Raya University students who used registered and active Android-based smartphones from 2017 odd semester until 2018. The sampling method used was the non-probability sampling method with a total of 100 people. The sampling technique is done by purposive sampling. Hypothesis testing uses Structural Equation Modeling (SEM) analysis. Through the analysis of indirect influence data, only product quality has a significant effect on loyalty through student satisfaction at the University of Bandung Raya. Whereas through direct influence, obtained only brand image and satisfaction that have a significant effect on loyalty within the University of Bandung Raya students.